Nutritional and physical characteristics of noodles incorporated with green seaweed (Ulva reticulata) and fish (Pangasianodon hypophthalmus) mince - Debbarma, Jesmi; Viji, P.; Rao, B. M.; Prasad, M. M. (Indian Journal of Fisheries, 2017)
Nutritional and physical properties of noodles incorporated with green seaweed (Ulva reticulata) puree and fish (Pangasionodon hypophthalmus) mince were evaluated. Four lots of noodles were prepared using different formulations viz., control noodle without adding seaweed puree or fish meat (C); noodle with 20% cooked pangasius fish meat (T1), noodles with 20% seaweed puree (T2) and noodles with 10% seaweed puree and 10% cooked pangasius fish meat (T3). Proximate composition, cooking properties, textural and sensory qualities of noodles were assessed. Results indicated that addition of green seaweed puree increased the crude fibre content of noodles. Crude fibre content was higher in T2 (2.62±0.18%) followed by T3 (1.71±0.06%). Cooking time for noodles varied between 6.80±0.71 and 9.15±0.21 min and cooking loss was significantly (p<0.05) higher for noodles with 20% seaweed puree. Significantly higher water absorption was noticed in noodles with 20% green seaweed puree, which led to softer and spongier textural intensities of the noodles. Although T2 showed lower score for colour values, its overall score for flavour and taste was higher compared to control and other treatments. The results indicate that incorporation of green seaweed puree in noodles has positively influenced the flavour and fibre content and hence, it can be used to enrich the fibre content of noodles.